Set Rot of Dalbergia sissoo Rooted Cuttings - Harsh, N. S. K.; Gupta, H. K.; Shukla, A. N. (Indian Forester, 2003)
A new set rot disease of rooted cuttings of Dalbergia sissoo caused by Fusarium equiset has been described. The disease was found to be encouraged by excessive soil moisture as provided through channels around the raised beds. Soil drenching with 0.05% bavistin or benlate can control the disease when it is observed in beds. A preventive approach can be treating the root suckers for about 10 minutes in 0.1% solution of bavistin or benlate before putting them in rooting medium.